Isospora brasilsatoae n. sp. (Apicomplexa: Eimeriidae) from thrushes Turdus spp. (Passeriformes: Turdidae) from Brazil - Oliveira, Mariana S.; Oliveira, Jhon Lennon G.; Rodrigues, Mariana B.; Silva-Carvalho, Lidiane Maria; Andrade, Lucas De Assis S.; Cardozo, Sergian V.; Ferreira, Ildemar; Berto, Bruno Pereira (Zootaxa, 2019)
A new species of coccidia (Protozoa: Apicomplexa: Eimeriidae) found parasitizing the yellow-legged thrush Turdus flavipes (Vieillot, 1818), the pale-breasted thrush Turdus leucomelas Vieillot, 1818 and the creamy-bellied thrush Turdus amaurochalinus Cabanis, 1850 in Southeastern Brazil is described. Isospora brasilsatoae n. sp. has oocysts that are ovoidal to pyriform, 26.8 × 21.1 μm, with smooth, bilayered wall, 1.6 μm thick. Micropyle present. Oocyst residuum absent, but one to three polar granules are present. Sporocysts are elongate ovoidal, 18.1 × 10.5 μm. Stieda body knob-like and sub-Stieda body trapezoidal. Sporocyst residuum is composed of granules that appear to be membrane-bounded. Sporozoites are vermiform with refractile bodies and striations. This is the ninth description of an Isospora sp. parasitizing a New World thrush.